2013
DOI: 10.1136/thoraxjnl-2013-204667
|View full text |Cite
|
Sign up to set email alerts
|

Management dilemmas in acute pulmonary embolism

Abstract: BackgroundPhysicians treating acute pulmonary embolism (PE) are faced with difficult management decisions while specific guidance from recent guidelines may be absent.MethodsFourteen clinical dilemmas were identified by physicians and haematologists with specific interests in acute and chronic PE. Current evidence was reviewed and a practical approach suggested.ResultsManagement dilemmas discussed include: sub-massive PE, PE following recent stroke or surgery, thrombolysis dosing and use in cardiac arrest, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
13

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 119 publications
1
43
0
13
Order By: Relevance
“…It is also unknown whether asymptomatic pulmonary embolism accounts for the majority of the excess pulmonary embolism. Demonstration of unsuspected pulmonary embolism occurs in up to 5% of thoracic computed tomography scans performed for non-pulmonary embolism indications, the majority in the context of malignancy [36]. However, our study has shown that the number of patients receiving thoracic computed tomography scans has increased over time in patients with and without cancer.…”
Section: Pulmonary Vascular Diseases | J De Miguel-díez Et Almentioning
confidence: 63%
“…It is also unknown whether asymptomatic pulmonary embolism accounts for the majority of the excess pulmonary embolism. Demonstration of unsuspected pulmonary embolism occurs in up to 5% of thoracic computed tomography scans performed for non-pulmonary embolism indications, the majority in the context of malignancy [36]. However, our study has shown that the number of patients receiving thoracic computed tomography scans has increased over time in patients with and without cancer.…”
Section: Pulmonary Vascular Diseases | J De Miguel-díez Et Almentioning
confidence: 63%
“…Condliffe and colleagues consider previous ischemic stroke not to be an absolute contraindication to thrombolysis, but at the moment there are no data to guide an acceptable timescale since the stroke [20].…”
Section: Dvt Prophylaxis and Therapy Of Pe In Ischemic Strokementioning
confidence: 99%
“…The risk-benefit ratio for individual patients should be assessed; however the general approach is to anticoagulate all patients with a cerebral infarct and PE. In patients with PE and a primary hemorrhagic stroke or recent significant hemorrhagic transformation, it is possible to consider inferior vena cava filter insertion and delayed anticoagulation [20]. Venous filter are usually placed in the infrarenal portion of the inferior vena cava.…”
Section: Dvt Prophylaxis and Therapy Of Pe In Ischemic Strokementioning
confidence: 99%
“…Le sugammadex pourrait être envisageable de neutraliser les molé cules d'un curare sté roïdien en cas de suspicion d'accident allergique lié à celui-ci en masquant l'allergè ne responsable, en l'occurrence l'ion ammonium quaternaire [2]. Mais derniè rement, un cas clinique a montré l'absence de ré version franche des signes de choc anaphylactique au rocuronium aprè s l'injection de sugammadex [3]. L'adré naline, donné e le plus pré cocement possible, à doses titré es, reste le mé dicament à administrer sans dé lai et en premiè re intention [4].…”
unclassified
“…La survenue d'une embolie pulmonaire massive aprè s une chirurgie ré cente constitue un dilemme pour la thrombolyse. Le risque hé morragique des fibrinolytiques est trè s important dans la premiè re semaine aprè s une chirurgie ré cente [3]. Les recommandations dans ces cas sont fondé es que sur des é tudes observationnelles.…”
unclassified